1981
DOI: 10.1017/s0022112081002449
|View full text |Cite
|
Sign up to set email alerts
|

Velocity field in a steady breaker

Abstract: An experimental investigation is described of the velocity field in a steady, spillingtype breaker, generated on a steady current by a submerged hydrofoil. Velocities have been measured with a laser–doppler system, and analysed with respect to mean and r.m.s. values as well as Reynolds stresses. The results indicate that the turbulent flow field downstream of the initiation of the separation at the surface resembles that in a self-similar turbulent wake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 4 publications
3
21
2
Order By: Relevance
“…As the waves break, k −3 shifts to k −5/3 because two-dimensionality of the flow is now complemented by 3D turbulent small scales formed by breaking events, and energy is quickly dissipated following the cascade process. The transition from steeper slopes to the standard Kolmogorov K41 slope is a well-known feature of breaking waves, with the transition in energy spectrum slopes from −3 (2D turbulence) to −5/3 (fully developed 3D turbulence) noted by a number of authors (Lemmin et al 1974;Battjes & Sakai 1981;Hattori & Aono 1985;Schlicke 2001) is predicted here, too. In Battjes & Sakai (1981), the slopes were found to scale with k −3 near the breaking point and with −5/3 further downstream, because the waves were spilling breakers.…”
Section: Energy Spectrasupporting
confidence: 63%
“…As the waves break, k −3 shifts to k −5/3 because two-dimensionality of the flow is now complemented by 3D turbulent small scales formed by breaking events, and energy is quickly dissipated following the cascade process. The transition from steeper slopes to the standard Kolmogorov K41 slope is a well-known feature of breaking waves, with the transition in energy spectrum slopes from −3 (2D turbulence) to −5/3 (fully developed 3D turbulence) noted by a number of authors (Lemmin et al 1974;Battjes & Sakai 1981;Hattori & Aono 1985;Schlicke 2001) is predicted here, too. In Battjes & Sakai (1981), the slopes were found to scale with k −3 near the breaking point and with −5/3 further downstream, because the waves were spilling breakers.…”
Section: Energy Spectrasupporting
confidence: 63%
“…The vertical thickness of the wake increased according to the square root of the distance behind the wave. Battjes and Sakai (1981) found that the region downstream of the breaker has a high degree of selfsimilarity in the mean velocity, turbulence intensity and shear layer, similar to a wake.…”
Section: Introductionmentioning
confidence: 94%
“…Far away from the breaker, the relation suggests an inversion of the relationship between the fluctuating components, especially near the surface. Several researchers used a submerged hydrofoil to generate spilling-type breakers (Duncan, 1981;Battjes and Sakai, 1981). Duncan (1981) used a towed hydrofoil and found that the breaking produced a shearing force along the forward face of the wave.…”
Section: Introductionmentioning
confidence: 99%
“…the jump height Froude number, with u fit c 1:1=Fr 2 Dh being the best fit to the experimental measurements. This trend indicates that, for a constant speed of the fast stream, the thinner the mass of stag nant water resting on the shear layer, the slower the large vortices move.…”
Section: Convective Velocity Of the Large Eddiesmentioning
confidence: 99%
“…Velocity fields in steady breakers have been obtained experi mentally by several authors [26,25,2,4,3,9,17,16]. However, in highly aerated regions, difficulties to obtain precise measurements arise.…”
Section: Introductionmentioning
confidence: 99%